2021
DOI: 10.5194/nhess-2021-343
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tsunami hazard in Lombok & Bali, Indonesia, due to the Flores backarc thrust

Abstract: Abstract. The tsunami hazard posed by the Flores backarc thrust, which runs along the northern coast of the islands of Bali and Lombok, Indonesia, is poorly studied compared to the Sunda megathrust, situated ~250 km to the south of the islands. However, the 2018 Lombok earthquake sequence demonstrated the seismic potential of the western Flores Thrust when a fault ramp beneath the island of Lombok ruptured in two Mw 6.9 earthquakes. Although the uplift in these events mostly occurred below land, the sequence s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Until now, a simulation of the propagation of the 1992 Flores tsunami located in the east of Labuan Bajo is the study conducted (Yeh et al, 1993). Afterwards, the potential for a tsunami in the north of the island of Bali, which is located west of Labuan Bajo, was simulated (Felix et al, 2021;Wibowo, Kongko, Hendriyono, & Karima, 2021). Another study showed the potential for a tsunami originating from Sletan Nusa Tenggara (Pradjoko & Muhari, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Until now, a simulation of the propagation of the 1992 Flores tsunami located in the east of Labuan Bajo is the study conducted (Yeh et al, 1993). Afterwards, the potential for a tsunami in the north of the island of Bali, which is located west of Labuan Bajo, was simulated (Felix et al, 2021;Wibowo, Kongko, Hendriyono, & Karima, 2021). Another study showed the potential for a tsunami originating from Sletan Nusa Tenggara (Pradjoko & Muhari, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we refined the GEBCO data using the Batnas data. As suggested by Felix et al (2022), we conducted a simple bathymetric data verification by comparing it with Google Earth satellite imagery to achieve good-quality data.…”
Section: Datamentioning
confidence: 99%
“…As an area that is prone to disasters, it is appropriate that Banyuwangi Regency needs to reflect on a number of natural disasters that have occurred in almost all regions in Indonesia, ranging from landslides, flash floods, tidal floods, hurricanes, volcanic eruptions, earthquakes, droughts, tsunamis, and so on. It is still clearly recorded in various records, major catastrophic events that occurred in 2018, such as the earthquake in Lombok Island, the tsunami in Central Sulawesi, and the tsunami in the Sunda Strait which claimed many lives and cause huge material losses (Felix et al, 2021;Fuady & Munadi, 2021;Safitri et al, 2021). A number of major disaster events that have occurred are a reminder for the government and all relevant stakeholders to continue to make improvements.…”
Section: Political Intervention and Disaster Risk Reductionmentioning
confidence: 99%